Natural Phonology: universal principles for the study of language (insiders meet outsiders) - Dziubalska-Kołaczyk, Katarzyna (My University, 2007)
Ever since Jakobson (or, shall we say, Plato?) linguists have been searching for universals (e.g. [1]). Their views on the role of universals in language and linguistics have varied widely, though. In this session we want to concentrate on the question of the existence of universal principles for the study of language. Natural Phonology has always advocated (cf. e.g. [2], [3], [4]) the holistic view on language, both in the sense of analyzing language structures (against ‘splendid isolation’ of any structure) as well as in the sense of seeing language as part of the universe. The latter means that the same principles of explanation apply to language and to other aspects of life, and thus they are derivable from the most general laws of human interaction with nature. In Natural Phonology the principles are cognitive, phonetic, psychological, sociological, etc. They lead to the establishment of linguistic preferences which guide the explanation of language-specific structures. Apart from Natural Phonology, many other theories refer to universals. Do they, however, look for universal principles of explanation? This is the core of the planned debate between the NP insiders and the outsiders wishing to take part.